THE EFFECT OF JACKFRUIT ADDITION (Artocarpus heterophyllus) ON CATFISH ABON (Pangasius hypophthalmus) TO THE CONSUMER ACCEPTANCE - Nurjanah, Siti; Sukmiwati, Mery; Sari, N Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted to determine the effect of jackfruit on catfish abon to consumer acceptance. The method used was experinmental completely and randomized design (CRD) that consists of 4 treatment levels: A0 (control: catfish abon without the addition of jackfruit), A1 (addition of jackfruit 20%), A2 (addition of jackfruit 40%), A3 (addition of jackfruit 60%). The parameters tested were organoleptic and proximate. The results showed that the addition of jackfruit 120 g (40%) in catfish abon was the best treatment and most preferable by 76 panelist (95%). Characteristics such a light brown color, distinctive aroma of fish began to decrease and not fishy, fibers texture soft were smooth and dry, savory taste and medium sweet, catsfish abon with jackfruit addition has 1.78% moisture, 22.03% protein, 13.53% fat, 3.20 % ash.Keywords: addition of jackfruit, catfish abon, consumer acceptance, chemical composition.